The Relationship of Breast Cancer Subtypes with the Event of Metastasis in Dr. M. Djamil Hospital Padang - Ahmad Fakhrozi Helmi; Daan Khambri; Rony Rustam (HM Publisher, 2021)
Background: One of the high mortality rates from breast cancer is related to the incidence of metastases. It is known that >90% of deaths in breast cancer are related to the incidence of metastases and the complications that follow. Breast cancer is divided into several subtypes based on the expression of receptor genes in breast cancer tissue, namely Luminal A, Luminal B, HER 2 and Triple Negative Breast Cancer (TNBC). This study aims to determine the relationship between breast cancer subtypes and the incidence of metastases in Dr. M. Djamil Padang. Methods: This study used a retrospective case-control study to breast cancer patients with metastatic at Dr M Djamil Hospital, Padang from 2016-2021. The research subjects were 260 breast cancer patients who met the inclusion criteria. The study subjects were divided into 130 patients as the case group with metastases and 130 patients as the control group with no metastases. To determine the relationship between breast cancer subtypes and the incidence of metastases, the chi-square test was used. If the p value <0.05, it can be concluded that it is significant. Furthermore, analysis is continued to obtain an odds ratio (OR) in identifying risk opportunities with Cochran's and Mantle-Haenszel statistics common odds ratio estimate. The data were analysed using the Statistical Package for Social Sciences (SPSS) program. Result: Characteristics of the subjects in this study can be seen that there is a relationship between hormonal contraception, T and N status with the incidence of metastasis (p <0.05). Patients with metastases were more common with breast cancer subtypes luminal B (61.5%), HER2+ (21.5%), TNBC (14.6%) and luminal A (2.3%). The most common locations for breast cancer metastases were lung (48.5%), bone (26.2%), liver (19.2%), brain (5.4%) and other places (0.8%). There was a relationship between breast cancer subtypes and the incidence of metastasis (p<0.038). The highest risk of metastases was in patients with TNBC subtype with OR = 7.74 (95% CI 1.72-34.79). There was no relationship between breast cancer subtypes with metastatic location (p>0.05) and breast cancer subtypes TNBC had a risk (OR) of 9.60 (95% CI 1.96-47.14) times increasing the risk of metastases in brain. Conclusion: It can be concluded that there was a relationship between breast cancer subtypes and the incidence of metastasis